2022
DOI: 10.1038/s41598-022-08903-9
|View full text |Cite
|
Sign up to set email alerts
|

A role for the periplasmic adaptor protein AcrA in vetting substrate access to the RND efflux transporter AcrB

Abstract: Tripartite resistance-nodulation-division (RND) efflux pumps, such as AcrAB-TolC of Salmonella Typhimurium, contribute to antibiotic resistance and comprise an inner membrane RND-transporter, an outer membrane factor, and a periplasmic adaptor protein (PAP). The role of the PAP in the assembly and active transport process remains poorly understood. Here, we identify the functionally critical residues involved in PAP-RND-transporter binding between AcrA and AcrB and show that the corresponding RND-binding resid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…Whereas the AcrB (Acriflavine resistance protein B) component in the AcrAB-TolC complex was recognized to be responsible for substrate recognition/transport and energy transduction [28–34], only the presence of the completely assembled tripartite multidrug efflux system confers a drug resistance phenotype. Recent studies indicated that also AcrA is involved in substrate binding and recognition [35]. In vitro tripartite AcrAB-TolC () and homolog MexAB-OprM structures have been elucidated via single-particle transmission- or cryo-EM [36–39].…”
Section: Drug Efflux Pumps In the Gram-negative Envelope Settingmentioning
confidence: 99%
“…Whereas the AcrB (Acriflavine resistance protein B) component in the AcrAB-TolC complex was recognized to be responsible for substrate recognition/transport and energy transduction [28–34], only the presence of the completely assembled tripartite multidrug efflux system confers a drug resistance phenotype. Recent studies indicated that also AcrA is involved in substrate binding and recognition [35]. In vitro tripartite AcrAB-TolC () and homolog MexAB-OprM structures have been elucidated via single-particle transmission- or cryo-EM [36–39].…”
Section: Drug Efflux Pumps In the Gram-negative Envelope Settingmentioning
confidence: 99%
“…The mutation of the identified conserved residues of each binding box completely destabilises an RND-based tripartite efflux pump, the AcrABZ-TolC assembly. These newly identified residues can be employed as novel therapeutic targets for the development of efflux pump inhibitors to combat antimicrobial resistance [37,39]. RND superfamilies are known for their role in virulence as well as resistance.…”
Section: Resistance Nodulation Cell Division (Rnd) Superfamilymentioning
confidence: 99%
“…According to structural studies, these four 3D sites correspond to nine distinct linear binding sequences known as binding boxes [37]. Additionally, the aforementioned study identified critical conserved residues within the binding boxes responsible for RND efflux pump functionality and further refined the exact residues of box4 (T271 and F292), box1 (R59) and box9 (K366) critical for efflux function [37, 39]. The mutation of the identified conserved residues of each binding box completely destabilises an RND-based tripartite efflux pump, the AcrABZ-TolC assembly.…”
Section: Types Of Bacterial Efflux Systemsmentioning
confidence: 99%
“…AcrAB–TolC works as an efflux pump for endogenous substrates such as bile salts, fatty acids and steroid hormones [7, 59]. The wide substrate specificity has been attributed to four channels: CH1 (low-molecular-mass drugs, β-lactams, NOV, phenicols), CH2 (high-molecular-mass drugs, macrolides, TETs), CH3 (planar aromatic cations) and CH4 (carboxylated drugs, including fusidic acid and β-lactams) () [60–62] and the sub-sets of binding amino acids in two binding pockets of AcrB (the proximal binding pocket and the distal binding pocket, separated by a switch-loop) [63–65]. The three proteins of AcrAB–TolC are encoded in two separate operons, acrAB and tolC-ygiAB (Table S2).…”
Section: The Role Of Rnd Multidrug Efflux Pumps In E Colimentioning
confidence: 99%